Validation of an aASPH-SNAP-tag fusion protein for immunodiagnosis of triple-negative breast cancer - Friedberg, Chardae (Department of Integrative Biomedical Sciences (IBMS), 2024)
Breast cancer is a serious health concern for women from as young as 20 years old and to this day is well known to be the leading cause of cancer incidences and mortalities in females. This disease is known as a heterogeneous disease that requires different systemic therapies, therefore early diagnosis and proper therapeutics are of utmost importance. The triple-negative breast cancer (TNBC) type is the most critical breast cancer subtype due to little to no expression present of the more commonly known breast cancer markers such as human epidermal growth factor receptor 2 (HER2), estrogen(ER) and progesterone (PR). This subtype was also found to have a 2-fold higher increased risk in individuals with African ancestry, intensifying the African breast cancer burden. Currently available diagnostics and therapeutics for TNBC are still a concern due to this subtype being associated with poor prognosis, a high metastasis rate and the ability to become easily resistant to available therapeutics due to an immunosuppressive tumour micro-environment and low immunogenicity. Therefore, a need to improve TNBC diagnosis and therapy is an urgent matter. Antibody technologies have been quite successfully applied to improve diagnostics and therapeutics for different diseases which include cancer. Limitations associated with the use of full-length antibodies have led to the development of antibody derivatives which includes single chain fragments of variability (scFv) where a heavy chain variable region of a full-length antibody would have been recombinantly fused to its light chain variable region. The SNAP-tag is commonly known as the engineered version of the human DNA repair enzyme O6 -alkylguanineDNA-alkyltransferase (AGT) that has the ability to recognize and bind to any benzyl-guanine modified substrates in a 1:1 stoichiometry. This makes SNAP-tag technology a favourable tool to use for studying the different properties of antibody derivatives. As part of this research, recombinant single chain fragment variables were recombinantly fused to SNAP-tag to generate a unique antibody format allowing to full exploit the specific binding activity of an antibody with the self-labelling ability of SNAP and create a versatile tool to develop recombinant immunodiagnostics and -therapeutics.